Financial Performance analysis on Financial Technology of Islamic Banking in Indonesia - Asri Noer Rahmi; Silvia Riska Pratiwi; Asep Dadan Suganda (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2022)
This research aims to analyze the effect of financial performance on financial technology in Islamic banking Indonesia. The measurement method used in this research the percentage of income derived from the financial technology in the financial statements presented in Islamic banking registered with the Financial Services Authority (OJK). The data used is secondary data obtained from the annual financial statements. Population in this research Islamic banking in Indonesia period 2016-2020. The sampling method in this research using purposive sampling method. The number of samples obtained is 60 samples. The data analysis used is the classical assumption test and multiple linear regression analysis. The method analysis data using SPSS version 25. The results of the analysis that has been carried out in this research, it shows that Return on Assets (ROA), Profit, and BOPO have a significant effect on financial technology in Islamic banking. Meanwhile, cash ratio and debt to equity ratio have no significant effect on financial technology but do contribute to the development of financial technology in Islamic banking in Indonesia. This research produces factors that influence the improvement of financial technology in Islamic banks in Indonesia. This research is the first research that examines the influence of financial performance on financial technology which has never been done before. The difference between this study and previous research are that the selected variables are a comparison of the results of previous studies that have a significant effect and there are variables that have not been studied by previous research and the sample period used is different from previous research is 2016 to 2020. Related on the difficulty of knowing the amount of financial technology through financial reports and there are banks that do not report the complete data needed for research.